SUSTAINABILITY REPORTING AND FIRM PERFORMANCE IN DEVELOPING CLIMES: A REVIEW OF LITERATURE - Hope Osayantin Aifuwa (Copernican Journal of Finance & Accounting, 2020)
The study basically examined the impact of sustainability reporting on firm performance in developing climes. A systematic content analysis approach was adopted in the study and it formed the basis for the researcher’s conclusion and recommendations. The findings of reviewed extant literature showed that there were inconclusive findings on the impact of sustainability reporting on firm performance. However, a large number of works submitted a positive relationship between sustainability reporting and firms’ performance. Secondly, financial performance measures often used by researchers include the profitability measures (ROA and ROE) and market-base measure (EPS and DPS), and the fourth version of the Global Reporting Initiative (GRI) framework in calculating sustainability disclosure index via content analysis. Thirdly, we also found that sustainability disclosure level was low in developing climes compared to other developed climes. We observed some methodological flaws in extant literature on the sector investigated and sample size employed. This study, therefore, recommended that further studies should be carried out on the impact of sustainability reporting on firms’ performance based on the suggested methodological improvement.